Built environmental profiles and children’s body mass index: A national data linkage study in Wales - Davies, Jo; Bailey, Rowena; Fry, Richard; Pedrick-Case, Rebecca; Stratton, Gareth; Pouliou, Theodora; Mizen, Amy; Watkins, Alan; Lyons, Ronan; Griffiths, Lucy (International Journal of Population Data Science, 2025)
Objectives This study aimed to identify environmental profiles of households with children across Wales and to examine the association between environmental characteristics and children’s weight status at ages 4 and 5. Methods Geographic Information System (GIS) metrics and environmental characteristics were applied to the households of children with a Body Mass Index (BMI) measurement recorded in the Wales Child Measurement Programme (CMP) between 2013 and 2019. BMI UK1990 clinical reference standards were used to categorise children as living with a “healthy” (≥second to <91st centile) or “unhealthy” (≥91st centile) weight. Profiles of home environments were determined using latent class analysis. Characteristics of the best model were examined to determine if they were meaningful qualitatively in the context of children’s environments. Logistic regression evaluated the association between the latent profiles and weight status. Results A total of 167,789 unique households were identified from the residences of 214,947 children who had a BMI measurement in the CMP. These households were separated into five profiles: ‘Rural, spacious and isolated’, ‘Suburban’, ‘Deprived and underserved’, ‘Deprived and well-served’, ‘Dense, coastal, well-connected’. Profile membership was associated with weight status; for example, children residing in ‘deprived, well-served’ areas were 22% more likely to be living with an unhealthy weight compared to children living in ‘rural, spacious and isolated’ areas. Conclusion Findings demonstrate the importance of research examining aggregate effects of children’s environments on unhealthy weight. Policy and practice needs to focus on those features which are modifiable to increase opportunities for healthier lifestyles.